Phytochemical screening, antioxidant and antibacterial activities of citrus hystrix leaves / Syafiqah Alya Samlin - Samlin, Syafiqah Alya (Faculty of Applied Sciences, 2017)
Phytochemical screenmg, antioxidant and antibacterial activities, Citrus hystrix leaves have been studied. Different polarities of extraction solvents are used which are hexane, chloroform and ethanol. Ethanol crude gave the highest percentage yield (3.14%) followed by chloroform and hexane. Secondary metabolites which are flavanoid, alkaloid, sterol, steroid, tannin, phenol, terpenoid and glycoside are presence in ethanol crude extract except saponin. Antibacterial activities against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Salmonella typhi were conducted. Disc diffusion method gave a result of highest inhibition zone by hexane crude extract against S. aureus ( 17 mm) while E.coli has no inhibition zone against chloroform and ethanol. TLC analysis conducted by using hexane and chloroform as the combination of solvent system with ( 1 :9) ratio gave the best separation of compound under long (365 run) and short (254 run) wavelength of UV lamp. The most antioxidant compounds were traced in ethanol crude extract by using thin layer chromatography (TLC) bioautography.